A bibliometric and thematic study of tissue engineering research and development in Malaysia by using online databases - Ahmad Radzi, Muhammad Aa'zamuddin; Zainuddin, Zainul Ibrahim; Hashi, Abdurezak Abdulahi; Sha'ban, Munirah (2016)
Purpose: The study aimed to examine Malaysian contributions in the field of tissue engineering (TE). This serves to fill the dearth of literature that systematically addresses the trend of TE research and development in Malaysia.